RATIONAL CHOICE OF Β-ADRENOBLOCKERS IN CHRONIC HEART FAILURE THERAPY - M. L. Maximov (Рациональная фармакотерапия в кардиологии, 2015)
There were presented results of clinical trials on β-adrenoblockers usage in patients with chronic heart failure (CHF) as well as data of own study on nebivolol efficacy and tolerability in 113 patients with ischemic heart disease, complicated with CHF. It is emphasized that therapy with β-adrenoblockers positively influences on cardiac hemodynamics and CHF symptoms, significantly reduces mortality risk and the frequency of hospitalizations. The usage of β-adrenoblockers is indicated in CHF of any stage. Efficacy of metoprolol, bisoprolol and carvedilol had been proven in CHF therapy. Nebivolol was effective in elderly patients with CHF.